FIGURITAS DALAM POLITIK LOKAL (STUDI: KETERPILIHAN CALON LEGISLATIF DI KABUPATEN TUBAN TAHUN 2014) - Amin, Ahmad Al; Azhar, Muhammad Ali; Bandiah, Bandiah (Jurnal Nawala Politika; 2016, 2016)
ABSTRACK figure is the first factor in winning the general election. These factors capable of delivering from PKB party seat legislative council in the district of Tuban. This study aims determine as far as of influence the PKB candidate figure legislative to give winning in district of Palang while 1999-2014. This study uses qualitative research method by study elected legislative candidate. Sources data in this study uses primary sources and secondary sources. Technical gathering data can do by serious interview with informants has determined and gathering documents are related to study material. The findings in this study that, the PKB party victory in the District Cross Rofi'udin pioneered by figures who have achievements and the idea of renewal in the art of Islam. Among them is the art of propaganda tongklek and social activities undertaken by the students MA Al-Mustofawiyah. Tongklek art is a means to draw attention to more mature voters, whereas in social service conducted targeted at first-time voters. Conclusion from this study is influence the figure Rofi’uddin selected because of there are image has given from society by means of achievement, contribution to NU along with entrusted missionary endeavor from Kiai. Meanwhile, in sphere NU still trust with the mean sendikoh dawoh marang Kiai (all of command from Kiai is doing by Santri and society). Keyword: figure, NU, legislative general election in district of Tuban 2014.